Recent Advances in the Synthesis of BiFeO3 Composites as Photocatalysis: Challenges and Opportunities - fattahi, Marzieh (Journal of Composites and Compounds, 2023)
Bismuth ferrite (BiFeO3) is a widely studied multiferroic material with strong ferroelectric and magnetic properties, making it highly suitable for applications in sensors, actuators, and energy storage. The development of BiFeO3 composites has gained significant attention due to their enhanced functional properties compared to pure BiFeO3. Various synthesis techniques, including sol-gel processing, hydrothermal synthesis, and solid-state reactions, have been explored to optimize structural, electrical, and magnetic characteristics. The review also explores the applications of BiFeO3 composites as photocatalysis, highlighting recent breakthroughs and potential future directions. This overview provides insights into the current state of BiFeO3 composite synthesis and its implications for advancing multiferroic materials in modern technology.